Second dose of measles-containing vaccine coverage and associated factors among children aged 24–36 months in Gondar city, Central Gondar, Northwest Ethiopia, 2023 - Adisu, Molalign Aligaz; Bogale, Worknesh Akanaw; Alemu, Tewodros Getaneh (Frontiers in Public Health, 2024)
Background: Globally, measles caused 207,000 deaths per year in 2019. Ethiopia rises among the top ten countries in the world with the highest number of measles cases. However, the second dose of measles-containing vaccination (MCV2) coverage is still low. To increase the coverage, the government of Ethiopia launched a nationwide measles vaccination campaign. Despite this intervention, the coverage is still under the target, and there is scarce information in the study area. Therefore, this study aimed to assess MCV2 coverage and associated factors among children aged 24-36 months in Gondar City, Central Gondar, Northwest Ethiopia, 2023. Methods: A community-based cross-sectional study was conducted among 621 children aged 24-36 months using a systematic random sampling technique from April 25 to May 25. A pre-tested, interviewer-administered, and structured questionnaire were used and collected using Kobo Toolbox then transferred to Stata version 17 for further analysis. The binary logistic regression model was employed to identify factors and the presence of an association was declared using a p-value < 0.05. Likewise, an adjusted odds ratio with a 95% confidence interval was used to interpret the direction and strength of an association. Results: A total of 621 children with a response rate of 98.1% participated in the study. The coverage of the second dose of measles-containing vaccination was 75.68% (95% CI: 72.1-78.9).